2017
DOI: 10.1530/eje-16-1064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the management and comorbidities of acromegaly over three decades: the French Acromegaly Registry

Abstract: The majority of patients with acromegaly now have successful disease control thanks to the multistep management. The incidence of comorbidities following diagnosis of acromegaly is very low. Life expectancy is now close to that of the general population, probably owing to better management of the GH/IGF-I excess and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
127
2
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(177 citation statements)
references
References 45 publications
(68 reference statements)
30
127
2
12
Order By: Relevance
“…In addition, patients followed up in the long term show a shift away from cardiovascular disease to cancer as a leading cause of death 25,88,89 (LQ). A continuum of benefit results from normalizing GH and IGF1 levels, leading to improved outcomes of disease-related comorbidities and reduced mortality risk 25 .…”
Section: Mortalitymentioning
confidence: 99%
“…In addition, patients followed up in the long term show a shift away from cardiovascular disease to cancer as a leading cause of death 25,88,89 (LQ). A continuum of benefit results from normalizing GH and IGF1 levels, leading to improved outcomes of disease-related comorbidities and reduced mortality risk 25 .…”
Section: Mortalitymentioning
confidence: 99%
“…An improved disease control and a reduction of the proportion of patients with medically uncontrolled disease over time were also observed in the French Registry of Acromegaly (18). Registry data indicate that the proportion of patients who underwent radiotherapy as a second-line therapy decreased gradually over time, being replaced by medical therapy.…”
Section: Outcome Of Multimodal Treatmentmentioning
confidence: 69%
“…Of interest, in a modern Danish cohort, overall mortality risk was still increased, but only with about 30% compared to the background population, again primarily due to an increased cardiovascular mortality (17). Conversely, in the French Registry of Acromegaly, life expectancy was close to the general population, SMR 1.05 (95% CI: 0.70-1.42), and cancer occurred just in 10% of patients, but most deaths were related to malignancies (18). Lastly, a recent systematic review and meta-analysis, showed that mortality was increased in the studies published before 2008, but did not differ from the general population (SMR: 1.35 (95% CI: 0.99-1.85)) in studies published after 2008.…”
Section: Epidemiologymentioning
confidence: 96%
See 2 more Smart Citations